Perancangan Motion Graphic (Bumper In) dan Video Dokumenter Permainan Tradisional Jawa Barat (Analisis Deskriptif Permainan Tradisional Pada Sanggar Seni Tikukur Majalengka) - Algiffari, Muhammad (LPPM BSI Bandung, 2015)
ABSTRACTTraditional games is part of local culture which have a lot of meaning, philosophy, and value inside. Recently traditional games was rarely played by children especially in West Java. There were several reason that cause the traditional games was left by the children such as, the development of modern technology is rapidly increasing, lack of open space for a children to play, and lack of parental supervision over the impact of the technology to their children. The purposes of motion graphic designed (bumper in) and documentary video of âKaulinan Baheulaâ become information traditional games of west java there are have a lot of benefit for motoric and psychology. The documentary video of âKaulinan Baheulaâ become information about being difficulties to found children who play traditional games.The design of the thesis uses descriptive analysis approach. Descriptive analysis means the process of taking a conclusion based on a specific cases become specific conclusion. Data collection techniques with interview, observation, literature study, and documentation. Motion graphic designed (bumper in) and documentary video of âKaulinan Baheulaâ is expected to provide information about traditional games in West Java, as well as the community can preserve the traditional games by lead our children to play traditional games in the future. Keywords: Motion Graphic, Bumper In, Documentary Video, Traditional GamesÂ ABSTRAKPermainan tradisional merupakan salah satu budaya lokal yang memiliki banyak makna. filosofi, dan nilai yang terkandung didalamnya. Saat ini permainan tradisional sudah jarang dimainkan dilingkungan anak-anak khususnya di Jawa Barat. Penyebabnya sangat kompleks seperti, peranan teknologi, kurangnya lahan untuk bermain anak, dan sikap para orang tua yang kurang memperhatikan dampak penggunaan teknologi pada anak. Tujuan dari perancangan motion graphic (bumper in) dan video dokumenter âKaulinan Baheulaâ dapat menjadi salah satu media informasi mengenai permainan tradisional di Jawa Barat yang memiliki banyak manfaat baik secara motorik juga psikologis. Video dokumenter âKaulinan Baheulaâ ini juga memberikan informasi mengenai mulai sulitnya ditemui anak-anak yang memainkan permainan tradisional.Perancangan tugas akhir ini menggunakan pendekatan analisis deskriptif. Deskriptif berarti proses mengambil suatu kesimpulan dari hal-hal yang bersifat khusus menjadi kesimpulan yang bersifat khusus. Teknik pengumpulan data dengan wawancara, observasi, studi pustaka, dan dokumentasi. Perancnagan motion graphic (bumper in) dan video dokumenter âKaulinan Baheulaâ diharapkan memberikan informasi mengenai permainan tradisional di Jawa Barat, serta masyarakat dapat melestarikan permainan tradisional dengan cara mengajak anak-anak untuk memainkannya kembali di masa yang akan datang.Kata kunci: Motion Graphic, Bumper In, Video Dokumenter, Permainan TradisionalÂ